Liver magnetic resonance relaxometry can provide useful markers for the assessment of right heart failure in dilated cardiomyopathy. (13th July 2021) - Rafouli-Stergiou, P; Symons, R; Droogne, W; Dresselaers, T; Masci, PG; Bogaert, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: In dilated cardiomyopathy (DCM) patients at risk of developing right heart failure (RHF), early depiction of congestive heart failure (CHF) is pivotal to inform about the hemodynamic status and tailor medical therapy. Purpose: We hypothesized that increased liver relaxation times measured at routine cardiovascular magnetic resonance (CMR), reflecting passive hepatic congestion, may be a valuable imaging biomarker to depict CHF. Methods: The study cohort included DCM patients with (n = 48) and without (n = 46) right ventricular dysfunction (RVD), defined as a right ventricular ejection fraction <35%, and >45%, respectively, and a control group (n = 40). Native T1, T2, and extracellular volume (ECV) liver values were measured on routinely acquired cardiac maps. Results: DCM with RVD patients had higher C-reactive protein, troponin I and NT-pro BNP values, and worse LV functional parameters than DCM without RVD patients (all p < 0.001). T1, T2 and ECV liver values were significantly higher in DCM with, compared to DCM without, RVD patients and also compared to controls [T1: 675 ± 88ms vs. 538 ± 39ms and 540 ± 34ms; T2: 54 ± 8ms vs. 45 ± 5ms and 46 ± 4ms; ECV: 36 ± 7% vs. 29 ± 4% and 30 ± 3%, respectively (all p < 0.001)]. Gamma glutamyltranspeptidase (γGT) correlated moderately but significantly with liver native T1 (r2 =0.34), T2 (r2 =0.27), and ECV (r2 =0.23) (all p < 0.001). Using right atrial pressure (RAP > 5 mmHg), as a surrogate measure of RHF, liver native T1 yielded at ROC analysis the highest AUC (0.906), significantly higher than liver ECV (0.813), γGT (0.806), liver T2 (0.797), total bilirubin (0.737) and alkaline phosphatase (0.561) [Figure 1]. A liver native T1 value of 617 ms showed a sensitivity of 79.5% and a specificity of 91.0% in identifying RHF. Density plots to discriminate between presence and absence of RHF are demonstrated at Figure 2. Excellent intra-/inter-observer agreement was found for assessment of native T1/T2/ECV liver values. Conclusion: In DCM patients, assessment of liver relaxation times acquired on a CMR exam, may provide valuable information with regard to the presence of RHF.